Beyond Compliance: Internal Control Systems and Public Financial Accountability in Salatiga City Governance - Juniarti; Rimi Gusliana Mais (Economics and Business Journal (ECBIS), 2026)
This study explores how the Salatiga City Government operationalizes principles of good governance and implements the Government Internal Control System (GICS), as reflected in the 2024 Local Government Financial Report– LKPD. The research also assesses how these mechanisms contribute to achieving Sustainable Development Goal (SDG) 16. Employing a descriptive qualitative approach, this study analyzes secondary data 2024 LKPD, performance accountability reports, and related internal control evaluations. This is complemented by triangulated insights from interviews with key government personnel. The findings reveal that Salatiga City has embedded core governance principles-transparency, accountability, and participatory engagement-within its financial reporting processes. The city's internal control system has reached Maturity Level 3 (Defined), indicating that control mechanisms are well-documented, institutionalized, and consistently applied. The use of digital reporting tools and community-based oversight further supports a culture of openness and accountability. The case of Salatiga City provides actionable insights for other local governments seeking to enhance financial governance. These practices directly support Indonesia's commitment to SDG 16, by fostering public trust and institutional integrity. This study adds to the emerging literature by integrating GICS analysis with local-level governance outcomes, not only to meet compliance standards but also to advance broader, effective, accountable, and inclusive development goals.